Optimal topology planning of electromagnetic waves communication network for underwater sensors using multi-objective optimization algorithms (MOOAs) - Shehadeh, Hisham A.; Jebril, Iqbal H.; Wang, Xiaopeng; Chu, Shu-Chuan; Idris, Mohd Yamani Idna (Automatika, 2023)
"Extremely High Frequency (EHF)" and "Very high frequency (VHF)" bands are mainly utilized with "Underwater Wireless Sensor Networks (UWSNs)" for communication purposes. However, due to the mobility of underwater sensors in water because of the water tide, the EHF/VHF signals may attenuate, lose or fade depending on the condition of the water. Therefore, it is a challenging stint of finding the optimal parameters of UWSN topology planning. In this paper, three "Multi-Objective Optimization Algorithms (MOOAs)" have been utilized to mitigate this problem, namely MOSFP, SPEA2 and NSGA-II. This work also intends to minimize path loss. On the other hand, it intends to maximize the power density of the network. Various network configurations, such as distance between sender and receiver, water conductivity and water permeability, are considered to evaluate the proposed objective models. Qualitative and quantitative tests have been conducted to analyze the results. From the analysis of the intersection point of Pareto-front of the objective functions, it is shown that all the algorithms find the optimal distance between transmitter and receiver, which balances the aforementioned maximization and minimization objective functions. This value is 36 m.